Handbook of research on discrete event simulation environments : technologies and applications - Abu-Taieh, Evon M. O.; El Sheikh, Asim Abdel Rahman (Hershey, PA : Information Science Reference, 2012)
'This book provides a comprehensive overview of theory and practice in simulation systems focusing on major breakthroughs within the technological arena, with particular concentration on the accelerating principles, concepts and applications'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Discrete-time systems -- Computer simulation